2010
DOI: 10.1007/s00221-010-2159-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of visual-evoked hemodynamic responses and potentials in human brain

Abstract: The interaction of brain hemodynamics and neuronal activity has been intensively studied in recent years to yield better understanding of brain function. We investigated the relationship between visual-evoked hemodynamic responses (HDRs), measured with near-infrared spectroscopy (NIRS), and neuronal activity in humans, approximated with the stimulus train duration or with visual-evoked potentials (VEPs). Concentration changes of oxyhemoglobin (HbO(2)) and deoxyhemoglobin (HbR) in tissue and VEPs were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…The fNIRS values retained for statistical analysis were changes in the averaged O 2 Hb and HHb computed over the 10 task blocks using the integral between 5 to 25 seconds out of the 30 seconds of the task. This integral analytic approach allows quantifying the concentration changes over time while being sensitive to task-related changes on O 2 Hb and HHb regardless of the shape of the hemodynamic response profile (Näsi et al, 2010;Safi et al, 2012). An index of hemoglobin differential (Hb diff = O 2 Hb -HHb) was also used to evaluate the level of cortical activation (Lu et al, 2015).…”
Section: Data Processingmentioning
confidence: 99%
“…The fNIRS values retained for statistical analysis were changes in the averaged O 2 Hb and HHb computed over the 10 task blocks using the integral between 5 to 25 seconds out of the 30 seconds of the task. This integral analytic approach allows quantifying the concentration changes over time while being sensitive to task-related changes on O 2 Hb and HHb regardless of the shape of the hemodynamic response profile (Näsi et al, 2010;Safi et al, 2012). An index of hemoglobin differential (Hb diff = O 2 Hb -HHb) was also used to evaluate the level of cortical activation (Lu et al, 2015).…”
Section: Data Processingmentioning
confidence: 99%
“…Since this discovery of the NIRS window (700–1300 nm) into the body, it has been widely used for measurement of tissue oxygenation. Part of those studies aimed to investigate various types of brain activation [2] due to stimuli as visual [3, 4], auditory [5, 6], motor [79] and more recently various cognitive [1014] ones. Other fields of application include studies of blood perfusion in muscles [1518] and in breast cancer [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63][64][65] Some others also have tried to correlate the ''fast'' signal or the Event-related optical signal 66 to VEPs. A study by Obrig et al showed coupling between fNIRS and VEP measures in response to a reversing checkerboard stimulus.…”
Section: Correlation Between Veps and Hbo Concentrationmentioning
confidence: 99%